Religious Soundscape and Intercultural Identity: A Study of the Sound of the Adhan, Church Bells, and Gamelan in Bandung, West Java - Henrycus Napitsunargo (International Journal of Nusantara Islam, 2026)
This study analyzes how Bandung's religious soundscape—the call to prayer, church bells, and gamelan—shapes spatial identity, religious experience, and intercultural relations in a pluralistic urban environment. Religious sounds here function beyond ritual: they generate social meaning and mediate everyday interfaith interactions. Using a qualitative case study design, the researchers collected data through soundscape observations, audio documentation, and in-depth interviews with diverse city residents. The analysis employed thematic analysis grounded in a posthuman acoustic framework. The findings suggest that religious soundscapes function as shared markers of time, space, and social identity. The call to prayer serves as a collective temporal marker; church bells reinforce historical spatial identity; gamelan embodies a sense of belonging to a local culture. Together, these auditory elements create a collective acoustic environment that fosters intercultural identification in urban space. The study also reveals shifts in sonic meaning driven by technological mediation: digital amplification, recording, and circulation can diminish perceptions of sacredness, transforming some sounds into functional rather than purely sacred sounds. By situating sound as a site of encounter, this research advances contemporary religious studies and the study of everyday religiosity. Its originality lies in integrating post-human soundscape and acoustic perspectives into the study of Indonesian Islam and in centering sound as a medium of religious-cultural interaction in a pluralistic urban context.